2003
DOI: 10.1016/s1387-3806(03)00262-8
|View full text |Cite
|
Sign up to set email alerts
|

Recent improvements of ISOLTRAP: absolute mass measurements of exotic nuclides at 10−8 precision

Abstract: In the past three years, the sensitivity and the performance of the Penning trap mass spectrometer ISOLTRAP have been enhanced significantly. These improvements, which range from technical developments to systematic studies of the various factors contributing to the uncertainty of the final mass result, now allow mass measurements of short-lived radionuclides with half-lives of less than 100 ms and with a precision of better than 10 −8 . Using a newly developed carbon cluster ion source, ISOLTRAP can perform a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The mass-resolving power R = m/δm that can be achieved with the TOF cyclotron technique is directly proportional to the cyclotron frequency and the duration of the quadrupolar excitation [5]:…”
Section: Setup and Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…The mass-resolving power R = m/δm that can be achieved with the TOF cyclotron technique is directly proportional to the cyclotron frequency and the duration of the quadrupolar excitation [5]:…”
Section: Setup and Techniquementioning
confidence: 99%
“…It has been in operation since the second half of the 1980s and has already been used to carry out mass measurements on more than 300 radionuclides [3,4]. Over the past few years, the efficiency and precision of ISOLTRAP have been significantly improved [5], thus making the experiment applicable for highprecision measurements on very short-lived nuclides as those required for this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By combination of elementselective laser ionization and high-resolution mass spectrometry we demonstrated not only resolution but also isolation of ground and excited states and prepared isomerically pure ensembles of 68 Cu and 70 Cu. To this end, the resonant ionization laser ion source (RILIS) [2] and the triple-trap mass-spectrometer ISOLTRAP [3][4][5] at ISOLDE/CERN [6] were used. Together withcoincidence studies this method allowed to determine the low-energy structure of 70 Cu and to unambiguously identify three -decaying isomers.…”
Section: Introductionmentioning
confidence: 99%
“…The mass of the ion of interest is obtained from the comparison of its cyclotron frequency with that of a well-known ''reference mass.'' The mass resolving power in the precision Penning trap is the product of the cyclotron frequency of the ion and the duration of the radio frequency (rf) excitation [16] and can reach 10 7 for medium-heavy nuclides and an excitation time of 10 s. After recent upgrades and improvements [16], calibration measurements using a carbon cluster ion source have shown that the limit of ISOLTRAP's overall relative uncertainty is now 8 10 ÿ9 [17].…”
mentioning
confidence: 99%